2019
DOI: 10.1148/radiol.2019181042
|View full text |Cite
|
Sign up to set email alerts
|

High-Spatial-Resolution Diffusion MRI in Parkinson Disease: Lateral Asymmetry of the Substantia Nigra

Abstract: NEURORADIOLOGY Parkinson disease (PD) is a neurodegenerative disorder characterized by progressive degeneration of dopaminergic neurons in the substantia nigra (SN), leading to abnormalities of movement and other functions. Motor symptoms in PD onset and progression have exhibited lateral asymmetry (1), which suggests that the neuronal loss in the SN can be asymmetric, as reported in a neuropathologic study (2). In a majority of patients, symptoms begin on the side of the dominant hand (1). SPECT has demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…Histopathologic studies have shown that 50%–70% of SN neurons have undergone apoptosis by the time motor symptoms appear. Asymmetric loss of dopaminergic neurons in bilateral SN may explain the symptom asymmetry [ 5 , 36 ]. Over half of PD patients show obvious differences in UPDRS III scores between the left and right limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathologic studies have shown that 50%–70% of SN neurons have undergone apoptosis by the time motor symptoms appear. Asymmetric loss of dopaminergic neurons in bilateral SN may explain the symptom asymmetry [ 5 , 36 ]. Over half of PD patients show obvious differences in UPDRS III scores between the left and right limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a common movement disorder and neurodegenerative disease [1] characterized by the loss of dopaminergic neurons [2][3][4][5] mainly in the substantia nigra (SN). Drugs and invasive treatments are the main therapeutic options for PD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MRI studies have revealed only slight or no gray matter atrophy in early to moderate stage PD patients, 7,56 although cortical CBF was decreased. 7 Although we did not observe significant changes in brain volume, ADC, or FA between α-synuclein and control mice, we did find, as reported for patients with PD, 57 a significant reduction in the ADC value in the substantia nigra of α-synuclein mice, highlighting the selective vulnerability of this region. Together, previous reports and the current data suggest that functional changes precede overt structural changes in PD.…”
Section: Discussionsupporting
confidence: 49%
“…Fractional Anisotropy (FA) in the posterior part seems to be the most discriminant feature ( 51 , 52 ). With the ADC for the whole SN, Zhong et al ( 53 ) found accuracy of 0.72, which is not sufficient in routine diagnosis. Interestingly, DTI metrics have also been used in a longitudinal approach, providing precious information on structural changes in the SN over the years ( 53 56 ).…”
Section: Diffusion Weighted Imagingmentioning
confidence: 99%